Anatomic Posterolateral Corner Reconstruction - Serra Cruz, Raphael (Arthrosc Tech, 2016)
Posterolateral corner injuries represent a complex injury pattern, with damage to important coronal and rotatory stabilizers of the knee. These lesions commonly occur in association with other ligament injuries, making decisions regarding treatment challenging. Grade III posterolateral corner injuries result in significant instability and have poor outcomes when treated nonoperatively. As a result, reconstruction is advocated. A thorough knowledge of the anatomy is essential for surgical treatment of this pathology. The following technical note provides a diagnostic approach, postoperative management, and details of a technique for anatomic reconstruction of the 3 main static stabilizers of the posterolateral corner of the knee.